ANALISIS PERMASALAHAN MOTIVASI BELAJAR DAN STRATEGI PENINGKATANNYA DALAM PEMBELAJARAN IPA DI SEKOLAH DASAR: STUDI LITERATUR - Elma Nafiatus Salamah; Septiani Putri; Syarifa Kamila; Wyne Vista; Delia Indrawati; Muh Syauqi Malik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the issues related to students’ learning motivation and the strategies to enhance it in science learning at the elementary school level. Learning motivation plays a crucial role in influencing students’ engagement and learning outcomes, particularly in science subjects that require active participation and a high level of curiosity. However, there are still students who exhibit low learning motivation due to teacher-centered instructional methods, limited variation in teaching models, and the lack of interactive learning media. This study employs a literature review method by analyzing ten relevant journal articles related to learning motivation and science education in elementary schools. The analysis is conducted to identify the factors contributing to low learning motivation as well as effective strategies to improve it. The findings indicate that learning motivation is influenced by both internal factors, such as interest and self-efficacy, and external factors, including teaching methods, learning environment, and teacher creativity. Various strategies have been proven effective in enhancing students’ learning motivation, such as cooperative learning models, Problem-Based Learning (PBL), the use of interactive learning media, and the implementation of ice-breaking activities in the learning process. Improving students’ learning motivation requires the application of innovative, student-centered instructional strategies, supported by a conducive  learning environment to achieve optimal science learning outcomes.